Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1302/0301-620x.95b2.30744
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of radiographic findings associated with hip dysplasia in a population-based cohort of 2081 19-year-old Norwegians

Abstract: In Norway total joint replacement after hip dysplasia is reported more commonly than in neighbouring countries, implying a higher prevalence of the condition. We report on the prevalence of radiological features associated with hip dysplasia in a population of 2081 19-year-old Norwegians. The radiological measurements used to define hip dysplasia were Wiberg's centre-edge (CE) angle at thresholds of < 20° and < 25°, femoral head extrusion index < 75%, Sharp's angle > 45°, an acetabular depth to width ratio < 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 23 publications
7
49
2
2
Order By: Relevance
“…10,18 Other studies used a less stringent cutoff of 25°and reported a prevalence of 4% to 23% in female European and Japanese cohorts. 10,17,42 The increased prevalence in the present study may be explained in part by differences in the technique used to measure LCEA. In the present study, the LCEA was measured to the lateral margin of the sclerotic line, 27 which, in some cases, can result in a smaller LCEA than measurements made to the lateral border of the acetabular rim.…”
Section: Kapron Et Almentioning
confidence: 99%
“…10,18 Other studies used a less stringent cutoff of 25°and reported a prevalence of 4% to 23% in female European and Japanese cohorts. 10,17,42 The increased prevalence in the present study may be explained in part by differences in the technique used to measure LCEA. In the present study, the LCEA was measured to the lateral margin of the sclerotic line, 27 which, in some cases, can result in a smaller LCEA than measurements made to the lateral border of the acetabular rim.…”
Section: Kapron Et Almentioning
confidence: 99%
“…A universal strategy with higher treatment rates did not seem to cause higher rates of AVN even though abduction treatment may place hips at risk. We have previously shown that based on existing cutoff values the prevalence of acetabular dysplasia (ie, at least 1 hip) ranges from 1.7% to 20% in this cohort, 18 with the lowest value based on the subjective assessment of the sourcil shape, and the highest value based on the borderline CE angle. The prevalence based on the dysplastic CE angle was 3.3%.…”
Section: Discussionmentioning
confidence: 78%
“…5 We chose to assess the most common quantitative measurements (ie, CE angle, FHEI, ADR, and Sharp' s angle), and also a subjective evaluation of dysplasia. 18 The strengths of our study include a large original RCT (11 925 infants) as the basis for this follow-up study, with standard protocols that remained unchanged throughout the whole RCT period. This maturity review also followed a highly standardized radiographic protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations